Description of Lysinibacillus telephonicus sp nov., isolated from the screen of a cellular phone - Rahi, Praveen; Kurli, Rashmi; Khairnar, Mitesh; Jagtap, Shubhangi; Pansare, Aabeejjeet N.; Dastager, Syed G.; Shouche, Yogesh S. (International Journal of Systematic and Evolutionary Microbiology, 2017)
A novel bacterial strain, designate dS5H2222(T), was isolated form the screen of a cellular phone. The cells were Gram-stainpositive, rod-shaped, aerobic and motile, and endospores are formed. S5H2222(T) grew as pale white colonies on trypticase soy agar and the best growth was observed at 37 degrees C (10- 55 degrees C) and at pH 7.0 (5.0-9.0). S5H2222(T) could tolerate up to 10% (w/v) NaCl. Phylogenetic analysis based on 16S rRNA gene sequences placed this strain within the genus Lysinibacillus and it exhibited high 16S rRNA gene sequence similarity to Lysinibacillus halotolerans LAM612(T) (97.8 %), Lysinibacillus chungkukjangi2RL3-2(T) (97.4 %) and Lysinibacillus sinduriensis BLB-1(T) (97.2 %). TheDNA- DNA relatedness of the strain with L. halotolerans JCM 19611(T), L. chungkukjangi KACC 16626(T) and L. sinduriensis KACC 16611(T) was 57, 64 and 55% respectively. The genomic DNA G+C content was 39.8 mol%. The major fatty acids of S5H2222(T) were iso-C-15:0, anteiso-C-15:0, iso-C-16:0 and anteiso-C-17:0. MK-7 was the only menaquinone and the main polar lipids were diphosphatidylglycerol, phosphatidylglycerol and phosphatidylethanolamine, four unidentified polar lipids were also present. The diagnostic amino acids in the cell wall peptidoglycan contained Lys-Asp (type A4 alpha). On the basis of the results of the phenotypic and genotypic characterizations, it was concluded that S5H2222(T) represents a novel species of the genus Lysinibacillus, for which the name Lysinibacillus telephonicus sp. nov. is proposed. The type strain is S5H2222(T) (=MCC 3065 T =KACC 18714(T)=LMG 29294(T)).

Domibacillus mangrovi sp nov and domibacillus epiphyticus sp nov., isolated from marine habitats of the central west coast of India - Verma, Ashish; Ojha, Anup Kumar; Dastager, Syed G.; Natarajan, Rameshkumar; Mayilraj, Shanmugam; Krishnamurthi, Srinivasan (International Journal of Systematic and Evolutionary Microbiology, 2017)
While studying culturable bacterial diversity in different marine habitats of the central west coast of India, two novel Gramstain-positive, strictly aerobic, motile, endospore-forming and rod-shaped bacterial strains designated as SAOS 44(T) and SAB 38(T) were isolated from mangrove sediment soil and the surface of a macroalga, respectively. The strains were taxonomically characterized by using a polyphasic approach and genomic methods. The phylogenetic analysis based on 16S rRNA gene sequencing placed the strains firmly in the genus Domibacillus and were most closely related to Domibacillus antri KCTC 33636(T). The predominant fatty acids were iso-C-15 : 0 and anteiso-C-15 : 0. The major polar lipids were diphosphatidylglycerol and phosphatidylglycerol in addition to an aminophosphoglycolipid. MK-6 was the only respiratory quinone. The range of values of digital DNA-DNA hybridization (19.2-24.9 %) and the ortho-average nucleotide identity (74.1-81.4 %) among strains SAOS 44(T), SAB 38(T) and other Domibacillus species clearly supports their status as a distinct and novel species for which the names Domibacillus mangrovi sp. nov. SAOS 44(T) (=DSM 100930(T)=KCTC 33820(T)=MTCC 12571(T)) and Domibacillus epiphyticus sp. nov. SAB 38(T) (=DSM 100929(T)= KCTC 33830(T)=MTCC 12575(T)) are proposed, respectively.

Development and evaluation of taxon-specific primers for the selected Caudovirales taxa - Newase, Sandeep K.; Gupta, Alka; Dastager, Syed G.; Kapadnis, Balu P.; Shashidhar, Ravindranath (Virus Research, 2019)
The phage taxonomy is primarily based on the morphology derived from Transmission Electron Microscopic (TEM) studies. TEM based characterization is authentic and accepted by scientific community. However, TEM based identification is expensive and time consuming. After the phage isolation, before analysis TEM, a DNA based rapid method could be introduced. The DNA based method could dramatically reduce the number of samples analyzed by TEM and thereby increase the speed and reduce the cost of identification. In the present work, four environmental phage isolates were identified based on TEM studies and genome size. The identification of these four phages was validated using DNA based method. The taxon-specific DNA markers were identified through multiple sequence alignments. The primers were designed at conserved genes (DNA polymerase or integrase) of 4 different phage taxa viz. family Ackermannviridae, genus Jerseyvirus, genus T4virus, and genus P22virus. These primers were evaluated using both in vitro and in silico approach for the amplification of the target taxons. Majority of the primer sets were found to amplify member species of the targeted taxa in vitro. In In silico analysis, six primer sets intended for identification of family Ackermannviridae showed positive amplification of >= 86.7% classified species. Further, the primers targeting the genus Jerseyvirus and T4virus showed the amplification of 53.8% and >= 84.6% species, respectively. The present work is a case study performed to explore the possibility of use of taxon-specific primers for identification and taxonomic studies of newly isolated phages to supplement the TEM.
Keywords: Bacteriophage; DNA markers; Pcr; Primers; Taxonomy; TEM

Distribution and bioprospecting potential of actinobacteria from Indian mangrove ecosystems - Manikkam, Radhakrishnan; Pati, Premalata; Thangavel, Shanmugasundaram; Venugopal, Gopikrishnan; Joseph, Jerrine; Ramasamy, Balagurunathan; Dastager, Syed G. (Microbial Diversity in Ecosystem Sustainability and Biotechnological Applications, 2019)
Actinobacteria are the ecologically and economically important prokaryotes with the unprecedented ability to produce novel metabolites. They are widely distributed in nature due to their physiological and metabolic versatility. Actinobacteria from marine ecosystem are recognized as a promising source for novel bioactive metabolites. Notably, mangroves are the most fertile and productive marine ecosystem due to their ecophysiological conditions and vast microbial diversity. At the global level, there are many novel actinobacteria which have been reported from mangrove ecosystems and also explored for their bioprospecting potential. However, in India, microbiologists have explored actinobacteria from selected mangrove ecosystems for the past five decades with special reference to culturable diversity and antimicrobial, antimycobacterial, anticancer, and enzymatic activities. So far, around 22 rare actinobacterial genera have been reported from the Indian mangrove ecosystems. However, several other novel actinobacteria with promising bioprospecting potential are yet to be explored. Hence, research on actinobacteria in the Indian mangrove ecosystem is still in its infancy. This chapter will describe the exploratory research work carried out on the importance, diversity, antimicrobial and enzymatic activity, biodegradation, and nanotechnological potency of actinobacteria from the Indian mangrove ecosystems. This chapter will enable researchers to identify the gaps to be bridged for further research on Indian mangrove actinobacteria and exploit their potential to the maximum benefit to mankind.

Deciphering taxonomic and functional diversity of fungi as potential bioindicators within confluence stretch of Ganges and Yamuna Rivers, impacted by anthropogenic activities - Samson, Rachel; Rajput, Vinay; Shah, Manan; Yadav, Rakeshkumar; Sarode, Priyanka; Dastager, Syed G.; Dharne, Mahesh S.; Khairnar, Krishna (Chemosphere, 2020)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">River confluences are interesting ecological niche with limited information in respect of the structure and the functions of diverse microbial communities. Fungi are gaining global attention as promising biological spectacles for defining the trophic status of riverine systems. We condense existing knowledge in confluence diversity in two Indian rivers (i.e. Ganges and Yamuna), by combining sediment metagenomics using long read aided MinION nanopore sequencing. A total of 63 OTU’s were observed, of which top 20 OTU’s were considered based on relative abundance of each OTU at a particular location. Fungal genera such as <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Aspergillus, Penicillium<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">, <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Kluveromyces, Lodderomyces,<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> and <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Nakaseomyces<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> were deciphered as potential bio indicators of river pollution and eutrophication in the confluent zone. <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">In silico<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> functional gene analysis uncovered hits for neurodegenerative diseases and xenobiotic degradation potential, supporting bioindication of river pollution in wake of anthropogenic intervention.

Design and development of multi-functional graphitic carbon nitride heterostructures embedded with copper and iron oxide nanoparticles as versatile sensing platforms for environmental and agricultural applications - Khasim, Syed; Pasha, Apsar; Dastager, Syed G.; Panneerselvam, Chellasamy; Hamdalla, Taymour A.; Al-Ghamdi, S. A.; Alfadhli, S.; Makandar, Mohammad Basha; Albalawi, Jalal Bassam; Darwish, A. A. A. (Ceramics International, 2023)
In the recent past, agrotechnology has witnessed a tremendous change due to the advent of technologies employed towards enhancing the yield and quality of the crops. The application of nanotechnology in agriculture is promoting sustainable practices and smart farming. Currently, nanomaterial-based sensors are gaining considerable attention in agrotechnology, such sensors can detect the environmental conditions and support for crop growth and enhances the agricultural yield. Graphiticcarbon nitride (g-C3N4), a soft polymer belongs to a class of 2-D semiconductors which are affordable, metal-free, indispensable for sensing applications due to significant changes in their conductivity upon exposure to analyte molecules in nano-regime. Further, this g-C3N4 can be combined with other nano metal oxides to form nanocomposites with remarkable properties and superior performance. In this work we report development of high-performance sensors based on graphitic carbon nitride embedded with copper and iron oxide nanoparticles. These heterostructures offers tremendous improvement in the physical and chemical properties due to the synergetic interactions between various phases. The chemiresistive sensor fabricated from these nanocomposites exhibit excellent sensitivity towards monitoring methane gas @ ppb level, relative humidity (% RH), and soil moisture content. Owing to their excellent sensitivity, stability and selectivity, this graphitic carbon nitride embedded with Cu and Fe oxide nanoparticles could be potentially used as multifunctional sensors towards environmental monitoring and greenhouse conditions in agricultural applications.
Keywords: Agricultural sensors; CuO nanoparticles; Environmental monitoring; FeO nanoparticles; Graphitic carbon nitride